Kajian Kepuasan Pasien Rawat Jalan di Wilayah Kerja Puskesmas Oesao Kabupaten Kupang: Outpatient Satisfaction Study in The Oesao Health Center Working Area, Kupang Regency - Yopinsias Endi Langga; Serlie K. A. Littik; Ribka Limbu (Yayasan Literasi Sains Indonesia, 2024)
Quality of health services is the perfection of health services according to applicable standards in achieving patient satisfaction. Data on outpatient visits at the Oesao Community Health Center over the last three years has decreased towards a low trend of 22,888 people, in 2019, 17,755 people in 2020, 9,432 people in 2021 and there are complaints of patient dissatisfaction about the service at the Oesao Community Health Center being less than optimal. The aim of the research was to examine the satisfaction of outpatients in the work area of ​​the Oesao Community Health Center, Kupang Regency. This type of quantitative research is descriptive design. The sample size was 35 respondents using consecutive sampling technique. Data was analyzed using Importance Performance Analysis (IPA). The research results show that the services at the outpatient installation at the Oesao Community Health Center are of high quality. The performance level score (X) is 0.86 and the level of importance or expectations (Y) is 1.46. The highest physical evidence of presentation is 99% and the lowest is 80%. The highest presentation reliability was 98% and the lowest was 92%. The highest presentation responsiveness was 92% and the lowest was 91%. The highest percentage guarantee is 95% and the lowest is 76%. The highest presentation empathy is 95% and the lowest is 90%. It is recommended that 3 attributes of the Oesao Community Health Center installation still require improvement, namely the knowledge of doctors, nurses, medicines and medical equipment is still lacking.